Empowering Local MSMEs in Purwakarta through AI-Based Market Intelligence (a Case Study at Ceramic Product) - Hetifah Sjaifudian; Nuzul Husnah; Nina Mardiana; Febryawan Yuda Pratama; M. Yani Syafei; Prattana Srisuk; Nina Rosida; Dede Kurniawan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This international community service program aims to empower local Micro, Small, and Medium Enterprises (MSMEs) in Purwakarta through the application of AI-based market intelligence, focusing on ceramic product MSMEs. Unlike conventional digital marketing assistance, this program emphasizes the development of market-sensing capability, customer insight, product positioning, and data-informed promotional planning. The activity was implemented through participatory training, guided practice, mentoring, and evaluation involving lecturers, students, an international academic partner, and local MSME actors. Participants were introduced to practical AI tools to identify customer segments, generate product narratives, analyze market opportunities, and develop promotional content for ceramic products. The results show that the program improved participants’ awareness of market-oriented decision-making and enhanced their ability to translate product uniqueness into customer-centered marketing messages. Participants were also able to develop simple customer personas, AI-assisted product descriptions, competitor observation notes, and digital content ideas. The activity demonstrates that AI-based market intelligence can be used as an empowerment instrument for MSMEs when introduced through simple, contextual, and practice-based methods. Continuous mentoring is recommended to strengthen digital confidence, improve content consistency, and support sustainable market expansion for local ceramic MSMEs.